PENGGUNAAN APLIKASI E-KINERJA SEBAGAI INSTRUMEN PENINGKATAN SASARAN KINERJA PEGAWAI PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SDM KOTA KENDARI - Karmini; Andi Syaiful Zainal; Andi Awaluddin Maruf (Halu Oleo University, 2024)
This study aims to evaluate the use of the E-Kinerja application as an instrument for improving Employee Performance Targets (SKP) at the Regional Personnel and Human Resource Development Agency (BKPSDM) of Kendari City. The methodology employed is qualitative, with data collected through semi-structured interviews and observations of the application usage process. Respondents were selected using purposive sampling, specifically, employees actively involved in the E-Kinerja application. The results indicate that the application enhances the effectiveness of performance assessment, with both leadership and employees experiencing benefits in terms of accuracy, transparency, and ease of data access. However, challenges such as technical issues and the need for ongoing training for employees persist. Additionally, other important indicators such as timely reporting, data transparency, accuracy in assessment, and employee satisfaction were identified as contributing factors to the effectiveness of the system. Recommendations include improving technological infrastructure, providing continuous training, and developing strategies to enhance the balance between quantitative and qualitative assessments. These steps are expected to further improve accountability and bureaucratic efficiency at BKPSDM Kendari City.